Alvaro Custodio and His Continuing Dream: The Teatro Clásico de Mexico in the 1960’s. - Dial, Eleanore Maxwell (Latin American Theatre Review, 1974)
Alvaro Custodio and His Continuing Dream: The Teatro Clásico de Mexico in the 1960’s.